Equivalent one-dimensional consolidation analysis involving vertical drains - Khoo, Wey En (2008)
An analytical method has been developed to simplify 3-dimensional analysis involving vertical drains into an equivalent 1-dimensional problem using an existing 1-D consolidation program, CONSOL. to predict the time required to achieve 909r consolidation. A conversion chart has been developed to obtain the equivalent coefficient of consolidation, cv*, to be used in CONSOL. The validity of this method is evaluated through comparison with results from conventional radial drainage method and field measurements. The two case studies show good agreement between the results obtained by conventional radial drainage method, equivalent 1-D consolidation method and field measured data. Lastly, a hypothetical problem is used to illustrate how this method can be used to determine the amount of surcharge and subsequent removal of fill in a soil improvement scheme.